Analisis Implementasi Si Black Berbasis Android Sebagai Upaya Peningkatan Prestasi Belajar Fisika - Ismatulloh, Kholida; Kholiso, Yosi Nur; Arianti, Baiq Desi Dwi; Ropikoh, Ropikoh (Kappa Journal, 2023)
This research aims to (1) produce Si Black-based learning media android (2) determines the level of appropriateness of learning media according to material experts, media experts, and users, (3) Efforts to improve the learning achievement of class VIII students on Asas Black. Implementation analysis research is collaborative research between quantitative research and product development. The initial product was validated by media experts and material experts and then revised. The next stage is user testing, and tested on 30 users from NWDI Middle School. Next, there was a summative test on 40 students at SMPN 3 Selong. Results research shows that (1) the Black product is very suitable for use in the physics learning process as proven by the average score by media experts of 93.5 and material experts of 91.25 in the "very good" category (2) the effectiveness of the product is proven through The increase in students' physics learning achievement reached an average pretest score in class VIIIa of 68.05 and VIIIb of 65.89 to a posttest of 83.05 and 81.05.